Effect of surface roughness on the microbiologically influenced corrosion (MIC) of copper 101 - Acharjee, Amit; Keskin, Yagmur; Peyton, Brent M.; Fields, Matthew W.; Amendola, Roberta (Frontiers in Materials, 2024)
The effect of varying surface roughness on microbiologically influenced corrosion by a model sulfate reducing bacterium Oleidesulfovibrio alaskensis G20 culture on copper 101 coupons was investigated using microscopic, spectroscopic and surface characterization techniques. After 7-day of anoxic exposure abundant biodeposits consisting of sessile cells and copper sulfide minerals were found and pitting attack was observed upon their removal. Results showed that the distribution and thickness of the biodeposits as well as the pitting severity were affected by the varying surface roughness. A direct relationship between surface roughness and microbial activity was not observed. However, a statistically significant reduction in the corrosion rate was recorded when the surface roughness was decreased from ∼2.71 μm to ∼0.006 μm.